PERANCANGAN SISTEM INFORMASI PEMBAYARAN SPP BERBASIS WEB PADA SMK FANIA SALSABILA KOTA JAMBI - M. Zahran Yudha; Muhammad Kevin Perdi Hasan; M. Ichwan Athallah; Dodo Zaenal Abidin (Jurnal Informatika Dan Rekayasa Komputer(JAKAKOM), 2023)
Information systems are very important for educational institutions to increase the competitiveness of schools with one another. The process of paying tuition fees at Fania Salsabila Vocational School, Jambi City, is still done by coming directly to school, this is not efficient both in terms of time and energy. In addition, the preparation of reports on receipt of spp payments is still being recapitulated using bookkeeping causing problems related to time. From the existing problems, a system is needed to facilitate tuition payments to student guardians. The system development method used is the Waterfall model, program modeling tools namely UML including use case diagrams, activity diagrams, and class diagrams. And the system is designed using the PHP programming language and MySQL database. This research resulted in a website-based spp payment information system that can assist schools in manage spp payments.